Escenarios para la innovación en la red agroalimentaria de carne bovina de Santo Domingo al año 2035. - Hernández Ordóñez, Cristian Germán (2021)
Ecuador has an outstanding beef production, since it allows it to fully cover local demand. However, in critical issues to internationalize its production, it has several drawbacks; Among these, the lack of coordination and disarticulation among the actors that make up the agri-food networks stands out. Therefore, the gap that exists in relation to other South American countries in communicational, technological, commercial and logistical aspects is accentuated. In the case of the province of Santo Domingo, the aforementioned weaknesses are present despite being an area with many resources to enhance its meat industry. For this reason, the objective of this research is to establish plausible scenarios for innovation in the Santo Domingo beef agri-food network by the year 2035. For this purpose, a robust and replicable methodological proposal has been proposed that, in addition to adopting methods of the French school of prospective and the Anglo-Saxon foresight, adds new consultation instruments and statistical tests that guarantee the fulfillment of the purposes of the study. As the main result, it was established that the desired scenario is governed by endogenous innovation criteria and favorable environmental conditions, highlighting key variables such as: innovation strategies, product quality, animal biotechnology, transition to the bioeconomy, changes in target preferences, local human capital formation, government incentives and local development programs.